PENGARUH PENGGUNAAN ALAT PERAGA PAPAN PERKALIAN UNTUK MENINGKATKA HASIL BELAJAR MATEMATIKA PADA SISWA KELAS III DI SDN INPRES RISA 1 - Asmawati; Abd Haris; Suciyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using a multiplication board as a teaching aid on improving mathematics learning outcomes for third-grade students at SDN Inpres Risa 1. The research employed a quantitative approach with an experimental method using a one-group pretest–posttest design. The sample consisted of all 23 students in the class, selected through total sampling. Data were collected through pretest and posttest essay questions (15 items) and analyzed using descriptive statistics, N-Gain calculation, normality test, and paired samples t-test with SPSS 26. The results showed that the average pretest score was 54.97, increasing to 79.42 in the posttest. The average N-Gain score was 0.54, categorized as moderate. The Shapiro–Wilk normality test indicated a normal data distribution (Sig. > 0.05), while the paired samples t-test revealed a significance value of 0.000 (< 0.05), indicating a significant improvement in students’ multiplication skills after using the multiplication board. This research confirms that concrete teaching aids can enhance student engagement, understanding, and achievement in mathematics learning.